Nickel and arsenite‐induced differential oxidative stress and antioxidant responses in two Anabaena species. (12th September 2018) - Prajapati, Rajesh; Yadav, Shivam; Atri, Neelam
Abstract : In recent years, release of chemical pollutants has increased due to anthropogenic activities. Heterocystous filamentous cyanobacteria constitute dominant paddy microflora and are excellent biofertilizers augmenting rice productivity. Cyanobacteria are frequently exposed to toxic metals, nickel and arsenic are one of the major toxicants present. We exposed two species of diazotrophic cyanobacteria Anabaena sp. PCC 7120 and Anabaena doliolum, to sub‐lethal concentrations (15.0 and 9.0 μM) of Ni 2+ and (17.0 and 11 mM) of arsenite (AsIII) and analyzed at different days of treatments (0, 1, 7, and 15 days) for oxidative damage and antioxidative biomarkers. Lipid peroxidation was enhanced (1.5‐ to 2.5‐fold increase in MDA content), indicating damaging effects of Ni 2+ and As(III) on membrane. Although Ni 2+ and As(III), both induced oxidative stress in both species, Anabaena PCC 7120 experienced less stress than A. doliolum . This could be explained by a higher activity of antioxidant enzymes catalase (CAT), ascorbate peroxidase (APX), glutathione reductase (GR) in Anabaena PCC 7120 (4.6‐, 2.0‐ and 1.4‐fold [Ni 2+ ] 3.2‐, 2.5‐, and 2.08‐fold [As]) compared to A. doliolum (4.2‐, 2.5‐, and 1.3‐fold [Ni 2+ ] and 3.2‐, 3.33‐, and 1.8‐fold [As]). Moreover, superoxide dismutase registered less inhibition in Anabaena sp. PCC 7120 (1.5 and 1.8) compared to A. doliolum (1.8 and 2.3) under Ni 2+ and As(III) stress. In addition to, IBR revealed that As(III) imposes severe impact on both strain, however, A. doliolum suffers most. Therefore, the study demonstrates interspecies variation in survival strategy of two Anabaena species and difference in potential of two different toxicants to produce oxidative stress.